Subarachnoid hemorrhage: tests of association with apolipoprotein E and elastin genes - Sauerbeck Laura; Flaherty Matthew; Kleindorfer Dawn; Kissela Brett; Sekar Padmini; Moomaw Charles; Xi Huifeng; Haverbusch Mary; Pal Prodipto; Woo Daniel; Kaushal Ritesh; Chakraborty Ranajit; et al. (BMC Medical Genetics, 2007)
Abstract Background Apolipoprotein E (APOE) and elastin (ELN) are plausible candidate genes involved in the pathogenesis of stroke. We tested for association of variants in APOE and ELN with subarachnoid hemorrhage (SAH) in a population-based study. We genotyped 12 single nucleotide polymorphisms (SNPs) on APOE and 10 SNPs on ELN in a sample of 309 Caucasian individuals, of whom 107 are SAH cases and 202 are age-, race-, and gender-matched controls from the Greater Cincinnati/Northern Kentucky region. Associations were tested at genotype, allele, and haplotype levels. A genomic control analysis was performed to check for spurious associations resulting from population substructure. Results At the APOE locus, no individual SNP was associated with SAH after correction for multiple comparisons. Haplotype analysis revealed significant association of the major haplotype (Hap1) in APOE with SAH (p = 0.001). The association stemmed from both the 5' promoter and the 3' region of the APOE gene. APOE ε2 and ε 4 were not significantly associated with SAH. No association was observed for ELN at genotype, allele, or haplotype level and our study failed to confirm previous reports of ELN association with aneurysmal SAH. Conclusion This study suggests a role of the APOE gene in the etiology of aneurysmal SAH.